Clinical utility of chlormadinone acetate (Lutoral™) in frozen‐thawed embryo transfer with hormone replacement. (9th May 2019) - Asada, Yoshimasa; Hashiba, Yoshiki; Hattori, Yukio; Inoue, Daichi; Ito, Rie; Fukunaga, Noritaka; Sonohara, Megumi
Abstract: Purpose: The clinical utility of chlormadinone acetate tablets (Lutoral™), an orally active progestin which has been available since June 2007, was compared to an in‐house vaginal suppository formulation of progesterone used between 2006 and 2007 for assisted reproductive technology (ART). Methods: We retrospectively evaluated the efficacy and safety of chlormadinone acetate by comparing the pregnancy rates and the incidences of birth defects and hypospadias in frozen‐thawed embryo transfer cycles using the in‐house vaginal progesterone and those using chlormadinone acetate for luteal phase support. Results: The pregnancy rates in the frozen‐thawed embryo transfer cycles were 31.2% (259/831) with vaginal progesterone for luteal phase support and 31.6% (4228/13 381) with chlormadinone acetate (no significant difference). In the cycles resulting in live birth following administration of chlormadinone acetate between July 2007 and December 2015, the incidence of birth defects was 2.8% (80/2893), and the incidence of hypospadias was 0.03% (1/2893). Conclusions: These results indicate that the pregnancy rate following frozen‐thawed embryo transfer using chlormadinone acetate for luteal phase support was comparable with that using vaginal progesterone, with no increased risk of birth defects, including hypospadias, which has been a concern following the use of progestins.